2010
DOI: 10.3961/jpmph.2010.43.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Socioeconomic Status and All-Cause Mortality After Breast Cancer Surgery: Nationwide Retrospective Cohort Study

Abstract: The socioeconomic status of breast cancer patients should be considered as an independent prognostic factor that affects all-cause mortality after radical mastectomy, and this is possibly due to a delayed diagnosis, limited access or minimal treatment leading to higher mortality. This study may provide tangible support to intensify surveillance and treatment for breast cancer among low socioeconomic class women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Korea's cancer epidemiology has similar features compared with the United States. For this reason, mutual discussion is ongoing about health inequalities due to the gap in SES (Khang and Kim, 2006;Park et al, 2010;Jung-Choi et al, 2011). In particular, low income and uneducated citizens do not fully benefit from anti-smoking programs, early cancer screenings, and technological development of medical treatment.…”
Section: Cancer Disparities and Communication Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Korea's cancer epidemiology has similar features compared with the United States. For this reason, mutual discussion is ongoing about health inequalities due to the gap in SES (Khang and Kim, 2006;Park et al, 2010;Jung-Choi et al, 2011). In particular, low income and uneducated citizens do not fully benefit from anti-smoking programs, early cancer screenings, and technological development of medical treatment.…”
Section: Cancer Disparities and Communication Inequalitiesmentioning
confidence: 99%
“…In particular, low income and uneducated citizens do not fully benefit from anti-smoking programs, early cancer screenings, and technological development of medical treatment. Thus, more attention is required for increasing patient cancer survival rate (Park et al, 2010;Viswanath et al, 2012). Cancer disparities refer to the health inequalities in cancer incidence and mortality that occur through social determinants .…”
Section: Cancer Disparities and Communication Inequalitiesmentioning
confidence: 99%
“…Second, there may have been a survival bias: if women with a lower SES are more likely to die after being diagnosed with breast cancer, analyses of cancer prevalence would tend to overestimate the correlation between SES and breast cancer. A previous study of Korean breast cancer patients demonstrated that the breast cancer survival rate of those in the highest SES category was 94.1%, while that of those in the lowest SES category was 85.7% [ 42 ]. When we reanalyzed our data with consideration of the 8.4% higher cancer prevalence in the lowest versus highest SES quartile, the association between educational level and breast cancer prevalence was robust.…”
Section: Discussionmentioning
confidence: 99%
“…We used health insurance status (MAP vs. NHI) and NHI premium level as a proxy for socioeconomic status. These indicators have been regarded as a highly reliable proxy for real income [29]. Hence individuals were classified into three groups: MAP recipients (extremely poor people who received livelihood assistance and were unable to pay for health care or insurance); NHI beneficiaries with a premium under 50%; and NHI beneficiaries with a premium at 50% or above.…”
Section: Methodsmentioning
confidence: 99%